Elaboration of the ether cleaving ability and selectivity of the classical pearlman's catalyst [Pd(OH)(2)/C]: concise synthesis of a precursor for a myo-inositol pyrophosphate - Mart, Alson; Shashidhar, Mysore S. (Tetrahedron, 2012)
The cleavage of propargyl, allyl, benzyl, and PMB ethers by Pd(OH)(2)/C can be tuned in that order, by varying the reaction conditions. Other moieties such as C-C double bonds, esters, trityl ether, p-bromo and p-nitrobenzyl ethers are stable to these reaction conditions. Cleavage of allyl ethers can be made catalytic by using 1:1 mixture of Pd(OH)(2)/C and Pd/C. The synthetic potential of the selective ether cleaving ability of Pd(OH)(2)/C, essentially under neutral conditions, has been demonstrated by an efficient synthesis of a precursor for the preparation of an inositol pyrophosphate derivative. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Ether cleavage; Inositol; Palladium; Protecting group